Daily and seasonal rhythms in immune responses of splenocytes in the freshwater snake, Natrix piscator. - Manish Kumar Tripathi; Ramesh Singh; Atanu Kumar Pati (PLoS ONE)
Present study was designed to examine daily and seasonal variability in the innate immune responses of splenocytes in the fresh water snake, Natrix piscator. Animals were mildly anesthetized and spleen was aseptically isolated and processed for macrophage phagocytosis, NBT reduction, nitrite production, splenocyte proliferation and serum lysozyme activity. Samples were collected at seven time points, viz., 0000, 0400, 0800, 1200, 1600, 2000 and 0000 h during three different seasons, namely summer, winter and spring. Cosinor analysis revealed that percent phagocytosis had a significant 24-h rhythm during summer and spring seasons. The peaks of rhythms in NBT reduction and nitrite release occurred in the morning hours at 10.88 h and 8.31 h, respectively, in winter. A significant 24-h rhythm was also observed in lysozyme concentration and splenocyte proliferation (both Basal and Concanavalin A stimulated) in all three seasons. A significant phase shift in splenocyte proliferation was obtained with a trend of delayed phase shift from winter to spring and from spring to summer. Of the nine variables, significant annual (seasonal) rhythms were detected in almost all variables, excluding phagocytic and splenosomatic indices. All rhythmic variables, except spleen cellularity, exhibited tightly synchronized peaks coinciding with the progressive and recrudescence phases of annual reproductive cycle. It is concluded that the snake synchronizes its daily and seasonal immune activity with the corresponding external time cues. The enhancement of immune function coinciding with one of its crucial reproductive phases might be helping it to cope with the seasonal stressors, including abundance of pathogens, which would otherwise jeopardize the successful reproduction and eventual survival of the species.